(untitled) (Web of Teachers: Inderscience Research, 2025)
New technologies and methods in the modern education system allow making the learning process interactive, effective and personalized. Artificial intelligence, virtual reality, online learning platforms, mobile applications, gamification and digital assessment tools deepen students’ knowledge, develop independent learning skills and improve the quality of education.